The cathelicidins LL-37 and rCRAMP are associated with pathogenic events of arthritis in humans and rats. - Hoffmann, Markus H.; Bruns, Heiko; Baeckdahl, Liselotte; Neregard, Petra; Niederreiter, Birgit; Herrmann, Martin; Catrina, Anca Irinel; Agerberth, Birgitta; Holmdahl, Rikard (Annals of the Rheumatic Diseases, 2013)
In rheumatoid arthritis (RA), neutrophil granulocytes fuel inflammation and damage tissue in the joint by releasing cytotoxic agents, antimicrobial peptides, proteases and other inflammatory mediators. The human cathelicidin LL-37 has recently been implicated in the development of systemic lupus erythematosus and psoriasis. To elucidate if antimicrobial peptides (AMPs) contribute to the pathogenesis of arthritis. Expression of LL-37 was determined in synovial membranes from patients with arthritis and control subjects. Expression of the rat cathelicidin rCRAMP and defensins was characterised in joints, blood and secondary lymphoid organs during pristane-induced arthritis (PIA) in rats and in a transfer model of PIA induced by CD4 T cells. Serum samples of rats with arthritis were tested for IgG and IgM autoantibodies against rCRAMP by immunoblot and for interferon (IFNα) by ELISA. Cathelicidins are strongly upregulated in RA synovial membranes and in joints from rats with arthritis as compared with healthy joints. Expression was most prominent in neutrophil granulocytes and macrophages/osteoclasts. Cathelicidin expression is also upregulated in the blood and spleen of pristane-injected rats, with strongest expression detected in activated CD62L- cells coexpressing granulocyte and monocyte markers. Pristane injection caused accumulation of low-density granulocytes in the blood. After pristane injection, the increased expression of rCRAMP coincided with higher levels of cell death, raised levels of interferon (IFN)α and development of autoantibodies. Our results show strong upregulation of cathelicidins and β-defensins coinciding with pathological events of arthritis. Higher expression and release of AMPs might contribute to development and/or maintenance of disease by systemic or local mechanisms. BACKGROUND OBJECTIVE METHODS RESULTS CONCLUSIONS